Delayed motor, mental and speech development and congenital brain malformations: the first description of Zhu–Tokita–Takenouchi–Kim syndrome in Russia - O. B. Kondakova; A. P. Gudkova; S. V. Demyanov; Yu. I. Davydova; A. A. Lyalina; D. I. Grebenkin; E. A. Bakovich; I. V. Kanivets; D. S. Demyanov; I. S. Zhanin; A. A. Pushkov; K. V. Savostyanov (Нервно-мышечные болезни)
Zhu–Tokita–Takenouchi–Kim syndrome (ZTTK syndrome) is a rare autosomal dominant nuclear speckleopathy characterized by developmental delay, hypotonia, intellectual disability, facial dysmorphism in association with variable brain malformations, musculoskeletal abnormalities and ocular involvement. Currently, 87 cases of ZTTK syndrome have been described worldwide. The syndrome caused by mutations in the SON gene, located on the long arm of chromosome 21 (21q22.11). Nonsense and frameshift mutations have been described in the SON gene. Missense mutations, partial or whole gene deletions are less common.The aim of the work is to analyze the clinical picture and molecular genetic results of patients with confirmed ZTTK syndrome and compare them with data from foreign literature.We observed the one boy and two girls with ZTTK syndrome aged 13 months to 59 months, averaging about 38 months. DNA diagnostic was performed by next generation sequencing. All patients and all parents were confirmed by Sanger sequening. Three pathogenic variants were identified: c.5753_5756delTTAG (p.Val1918Glufs*87), c.1531del (p.Thr511Glnfs*9) and c.403delG (p.Glu135Asnfs*14). The first one was is most common, the other two are novel variants. Most patients had growth, motor and speech delay, seizures, hypotonia, congenital heart defects, urinary tract abnormalities and brain malformations. Comparative analysis of facial features in patients with ZTTK syndrome showed downslanting palpebral fissures, epicantal folds, broad or depressed nasal bridge, flared nares, smooth philtrum, thin upper lip and low set, rotated ears. The use of next generation sequencing as a first‑line test for research and diagnostic of ZTTK syndrome is advisable due to the pronounced clinical polymorphism.